Crack Goes the Cascaron - Fajardo, Sara Andrea; Arreola Mendoza, Roco̕ (New York, NY : Knopf Books for Young Readers, 2025)
"Shell-abrate a joyous Latine tradition, with Toti and his family in this upbeat bilingual story, hatched in time for Easter. What are cascarones: Cascarones are empty egg shells that have been colored, filled with paper confetti, and sealed! The hunt is on to figure out who will be the reigning champ of Cascarones, and Toti knows that he has his family beat. His parents are too easy, they make old- school cascarones with confetti inside. His sister, Carlita wishes she could create cascarones like him, and his Abuela doesnt even stand a chance. When the day of Cascarones arrives, will Toti seize his moment or will it be scrambled when he learns someone has switched his cascarones for fake ones! With a cheeky twist at the end, readers will laugh and relish at the antics of Toti and his family in this exuberant bilingual story."--Provided by publisher.
Keywords: Eggshells -- Juvenile fiction; Outdoor games -- Juvenile fiction; Holidays -- Juvenile fiction; Family life -- Juvenile fiction; Easter -- Juvenile fiction; Families -- Juvenile fiction; Hispanic Americans -- Juvenile fiction; Picture book